LED based Fourier transform absorption spectroscopy of D216O in 14, 800–15, 200 cm−1 spectral region. (November 2017) - Vasilenko, I.A.; Naumenko, O.V.; Serdyukov, V.I.; Sinitsa, L.N.
Highlights: The parameters of the D2 16 O spectral lines in the range 14, 800–15, 200 cm −1 were determined for the first time. A total of 162 energy levels belonging to four vibrational states were retrieved. Observed positions deviate from most accurate variational calculations up to 0.8 cm −1 . Abstract: A study of the vibration-rotation absorption spectrum of the D2 O molecule in the range 14, 800–15, 200 cm −1 has been performed. The spectrum was recorded with the spectral resolution of 0.05 cm −1 using a Fourier Transform Spectrometer coupled to a multi-pass White-type cell providing an optical path length of 34.8 m. A light-emitting diode was used as the radiation source giving a high brightness that resulted in an S/N ratio of measurements of about 10 4 . A total of 162 energy levels belonging to four vibrational states were determined. The rovibrational assignment of 309 transitions attributed to D2 O was based on the variational calculations. The observed D2 16 O spectrum is, mainly, formed by transitions belonging to the 4ν1 + 2ν2 + ν3, 6ν1 and the 5ν1 + ν3 vibrational bands centered at 14, 979.173, 15, 049.52, and 15, 050.898 cm −1, respectively. It was found that the calculated line positions might deviate from the observed ones up to 0.8 cm −1 indicating the necessity of further optimization of the potential energy surface for the D2 16 O molecule.